Translation of neologisms in the sermon on the mount from the book of Matthew (5-7) of the Asante Twi Twerɛ Kronkron - Asamoah, Emmanuel Foster (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.